Conditional Constructions in Yemsa - Mitike Asrat; Girma Mengistu; Endalew Assefa (Дискурс)
Introduction. The main objective of this study is to produce a comprehensive description of Yemsa conditional constructions. The existing studies do not describe conditional clauses in Yemsa. This study aims to fill the gap in the description of the internal structure conditional clause of Yemsa.Methodology and sources. The data were collected through the elicitation technique through informant interviews about the conditional clause in Yemsa. The data were analyzed using a descriptive approach without considering any particular theoretical framework. The data was described and analyzed in light of general definitions and typological classifications of conditional constructions in the linguistic literature.Results and discussion. Antecedent and consequent clauses are attested. The morphemes occur in different types of conditional clauses. Canonical and non-canonical forms of conditional have been identified. The semantic-based classification of Yemsa conditionals is dealt with in light of Thompson et al.'s typological view. Real, unreal, counterfactual, hypothetical, concessive, and exceptive conditional are discussed. In Yemsa, the protasis of the real conditional clause type differs from the unreal protasis conditional clause type. A subordinate clause (the protasis) states some condition, the truth of which is not asserted, under which another main clause (the apodosis) holds.Conclusion. The study will provide some syntactic data to researchers in the comparative syntactic description of the Omoto languages about conditional clauses. It will serve as a good resource material for further theoretical studies concerning conditional constructions in general.